Howard Pyle's Robin Hood - Dunn, Joeming W.; Dunn, Ben; Pyle, Howard 1853-1911 (Edina, Minn. : Magic Wagon, 2008)
A comic adaptation of Howard Pyle's The merry adventures of Robin Hood which recounts the legend of Robin Hood, who plundered the king's purse and poached his deer and whose generosity endeared him to the poor.
1200L
Keywords: Robin Hood (Legendary character); Graphic novels; Graphic novels